The Influence of K-pop Concert Attractiveness on Fanaticism: Dual Mediation by Satisfaction of Idol and Promoter in Indonesia - Haditha Miftahul Sabrina; Ananda Sabil Hussein; Radityo Putro Handrito (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesia has become one of the largest markets for Korean popular music concerts, with billions of streams and sold-out events. This study explores how concert attractiveness affects fanaticism among Indonesian fans, using satisfaction with idols and satisfaction with promoters as mediating factors. The research draws on the idea that satisfaction grows when experiences meet or exceed expectations, turning initial appeal into lasting loyalty. The study uses a quantitative explanatory approach with purposive sampling. Surveys were collected from 250 fans who attended at least one Korean popular music concert between 2022 and 2024. Data were analyzed using structural equation modeling with partial least squares. Results show that attractiveness strongly influences both idol satisfaction and promoter satisfaction, which then drive fanaticism. The model explains 52 percent of idol satisfaction, 48 percent of promoter satisfaction, and 61 percent of fanaticism. Idol satisfaction has a stronger mediating effect than promoter satisfaction. Concert attractiveness alone is not enough to create fanaticism. It works through confirmed expectations that build satisfaction with both performers and event organizers. Idol-focused satisfaction plays the bigger role, but promoter quality remains essential for sustainable fan experiences.